An auction framework to integrate dynamic transmission expansion planning and pay-as-bid wind connection auctions - Niall Farrell; Mel T. Devine; Alireza Soroudi (The Economic and Social Research Institute (ESRI), 2016)
Efficient renewables deployment requires the minimisation of both internal generation costs and external transmission expansion planning (TEP) costs. Competitive pay-as-bid connection auctions allow wind energy generators to reveal their costs of generation such that internal generation costs may be minimised. TEP costs have not been incorporated into such auctions to date. Integrating these procedures may allow for a global minimisation of internal generation and external TEP costs over many time periods. This paper develops an auction mechanism and associated modelling framework to carry this out. The contributions of this framework are verified using a numerical example. Our results show that ignoring generation costs in transmission expansion planning has quantifiable economic consequences, while traditional pay-as-bid auctions can benefit from incorporating features associated with TEP, such as multi-period optimisation. Full integration of both modelling frameworks leads to efficiency improvements, both in terms of reduced investor rentseeking and a more efficient deployment path.
Keywords: 330; Renewable Energy; Electricity Transmission; Optimisation; Auction Design